Effect of melengestrol acetate (MGA) on cultured bovine muscle satellite cell proliferation and differentiation - Sissom, E.K.; Kayser, J.P.; Waylan, A.T.; Dunn, J.D.; Johnson, B.J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Melengestrol acetate (MGA) increases growth rate and inhibits estrus in feedlot heifers. Little is known of MGA’s effect on skeletal muscle growth and differentiation. The purpose of this trial was to investigate the potential direct effects of MGA on cultured bovine muscle satellite cell proliferation and differentiation. Satellite cells isolated from yearling cattle were used to assess the effect of MGA in a dose titration (0, 1 nM, 10 nM, 100 nM, 1 μM, 10 μM, and 100 μM) study on [3H]-thymidine incorporation. Likewise, satellite cell cultures were allowed to differentiate, and nuclei were stained at 168 hours to determine the effect of MGA (10 nM and 100 μM) addition during the first 48 hours on extent of differentiation and absolute myotube nuclei number. MGA addition resulted in a dose-dependent decrease (P<0.05) in DNA synthesis as measured by [3H]-thymidine incorporation. MGA addition (10 nM) did not significantly alter the extent of differentiation or myotube nuclei number at 168 hours in culture even though this concentration reduced DNA synthesis. However, 100 μM MGA addition significantly (P<0.05) reduced both fusion percentage and myotube nuclei number as compared to control cultures. These data suggest MGA addition at concentration between 10 nM and 100 μM affected bovine muscle cell proliferation and differentiation. A better understanding of these effects will increase our knowledge of bovine muscle growth and development.
Keywords: Beef; Melengestrol acetate (MGA); Satellite cell; Proliferation; Differentiation